Water Deficit Stress Tolerance Traits in Maize (Zea mays L.) and Identification of Tolerant Varieties - Lama, R.; Chakraborty, U. (International Journal of Bio-resource and Stress Management, 2023)
Water deficit (drought) during the summer season is one of the major production constraints for maize (Zea mays L.) in large areas of Southeast Asia. Identification and development of varieties capable of withstanding the stress conditions could be an ideal and affordable approach suitable for resource to poor maize-growing farmers of such areas. The present study was undertaken on artificially induced water stress of maize in vitro, where stress was applied with PEG-6000 on one week old seedlings of six varieties of maize-30V92, BN 1133, Kaveri-Super 244, BN 101, Dhanya and Swarna, and for 3, 5 and 7 days. Assay of antioxidative enzymes revealed that peroxidase activities decreased on the 7th day of water stress in BN 1133, Dhanya, 30V92 and Swarna but in BN 101 and Super 244 the activity increased with period of stress. Ascorbate peroxidase and superoxide dismutase activities increased initially and then declined. Catalase activity declined at all periods of stress in BN 1133, Dhanya, 30V92 and Swarna while the other two varieties showed an increase during stress. Chlorophyll content showed a decline during the period of drought when compared to the control plants of all varieties. With the increase in the intensity of drought there was an increase in both proline and ascorbate content in all varieties. H2O2 accumulation and lipid peroxidation showed an increase during stress in BN 1133, Dhanya, 30V92 and Swarna but no increase was seen in the other two varieties. Water stress induced decrease in RWC was greater in BN 1133, Dhanya and Swarna. Thus enzymatic activity and biochemical tests showed that BN 1133, Dhanya, 30V92 and Swarna are more susceptible to drought stress than KS 244 and BN 101 which are the tolerant varieties.